Assessing Competitiveness Using Industry Unit Labor Costs : An Application to Slovakia. (IMF Working Papers; Working Paper, 2012)
Conceptual ambiguities and statistical weaknesses hamper the assessment of external competitiveness. The term competitiveness, while applied extensively, is often imprecisely defined, which can result in analytical errors and mistaken policy advice. Furthermore, aggregate statistical measures of competitiveness in terms of exchange rate misalignment can be biased. To address these issues, this paper makes two contributions. First, it clarifies the external competitiveness concept, highlighting the dichotomy between productivity-driven long-run growth and short-run deviations from the underlying growth trajectory, which can be related to exchange rate misalignment. Second, it develops a disaggregated statistical approach for examining competitiveness based on unit labor costs at the three digit industry level in a group of comparable countries. The case of Slovakia is used to illustrate these concepts, but the analytical insights have general application.